COMMISSIVE AND DIRECTIVE ACTS PERFORMED BY DAVID CAMERON IN HIS DAVOS SPEECH - PRATAMA, NANDA BAGUS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Pragmatics, Commissive and Directive Acts, Davos Speech, David    Cameron. Pragmatics can be defined as a study talking about the relationship between language and context. It covers commissive and directive acts as the kinds of speech act. Commissive acts are acts that commit the speaker to some future course of action. While directive acts are acts that attempt by the speaker to get the addressee to do something. The writer takes a speech that David Cameron  has delivered in the World of Economic Forum (WEF) as the object of data. This study is aimed to know the types of commissive acts and also the types of directive acts performed by David Cameron in his Davos speech.This study uses qualitative approach to find out the answers of the problems. In collecting the data the writer had two steps, they are downloading the video and also the script, after that selecting the utterances which are the case of commissive and directive acts. The writer had four steps in analyzing the data, firstly, listing the selected utterances and putting it into table, secondly, identifying the type of selected utterances, then analyzing and discussing the data based on the theory proposed by Searle (1983), and the last is concluding the result of the data analysis.This study reveals that commissive acts are applied by the speaker in 25 utterances containing promising (17 utterances), warning (5 utterances), offering (1 utterance), and threatening (1 utterance). The directive acts are applied in 32 utterances containing suggesting (11 utterances), questioning (3 utterances), commanding (8 utterances), and requesting (10 utterances). Based on the finding it is known that David Cameron applied promising which is a kind of commissive acts in 17 utterances. Such a kind of commissive acts is mostly used by David Cameron in his Davos speech in order to promise the audiences about what he will do in the future. He also applied suggesting in 11 utterances which is a kind of directive acts. Such a kind of directive acts is mostly used by David Cameron in his Davos speech in order to advise the audiences because there are so many problems that G8 faced at that time so that the speaker tried to give solutions for them.The next researcher who will conduct the similar study in case of commissive and directive acts are suggested to find other objects to be analyzed like newspaper, advertisement, TV program, etc. They are also expected to conduct studies which involve other kinds of speech act such as representative, expressive, performative, and assertive acts, since those four types have not been studied by the writer.